MICROWAVE ABSORBING PROPERTIES OF LaMn1-x NixO3. - Sitti Ahmiatri Saptari; Azwar Manaf; Budhy Kurniawan (Jurnal Sains Materi Indonesia, 2014)
MICROWAVE ABSORBING PROPERTIES OF LaMn1-x NixO3. The doped lanthanum manganites have unusual magnetic and transport properties, which makes it possible for this material to be used for microwave absorbing. In this study, LaMn1-xNixO3 (x = 0, 0.02, 0.04, and 0.06) were prepared by solid state reaction method as microwave absorption material. The crystal structure and magnetic properties were characterized byX-Ray Diffractometer (XRD) and Vibrating SampleMagnetometer (VSM), respectively. Refinement results of X-Ray diffraction pattern using High Score Plus Software showed that the samples with various x = 0 to x = 0.04 had a single phase with monoclinic crystal structure, while the sample with x = 0.06 had two phases with monoclinic and hexagonal structures. Hysteresis loops showed that the LaMn1-xNixO3 (x = 0, 0.02, 0.04, and 0.06) samples are soft magnetic materials. Microwave absorption properties were investigated in the frequency range of 8-12 GHz using Vector Network Analyzer (VNA). An optimal reflection loss of -8.85 dB is reached at 11.58 GHz for x = 0.04 with sampel thickness of 2 mm.